Community Forests Ensuring Local Governance and Livelihood: A Case Study in Sunwal VDC, Nawalparasi, Nepal (Geographical Journal of Nepal, 2011)
This paper analyses local governance in forest resource management through people's participation and the ways it relates to the contribution in securing livelihood. This case study was conducted in Sunwal VDC of Western Tarai, Nepal, and information was collected through direct observation, household survey, key informant interview, focus group discussion and analysis of secondary information. It discusses a few examples of how the community forestry programme can be used as a means to promote participation of the women, the poor, disadvantaged and marginalized group in forest resource management, as well as enhancing livelihood and improving the forest resource management in their locality. It is found that though the community forestry programme has positive impacts, it faces several constraints and challenges. The results of the case study clearly indicate that community forestry processes must address the political, economic and social needs of the forest users, and also provide a neutral platform on which the poor and disadvantaged group can express their voices.The Geographical Journal of Nepal, Vol. 8-9, 2010-2011: 33-42